Escrituras creativas en la universidad. Algunas ideas, experiencias e indisciplinas - Elisondo, Romina Cecilia (Ñawi, 2023)
The objective of this paper is to reflect on the role of creative writing in the university. Our proposal is based on cognitive studies of creativity and current development on creative teaching. We present four experiences, in our opinion, of creative writing at the university: travel notebooks, paths of life, a class in a word and tips to become a creative scientist. Finally, we try to articulate creative writing, teaching, research and university connection. In the writing we take some licenses, we include images of the experiences and some brief stories. The text intends to challenge from questions and not answers or certainties. We seek, at least in part, to tell our experiences by appealing to different formats and modalities. We invite readers to generate creative spaces in the university where spaces are enabled for indiscipline, border writing and divergent actions.